Randomized Controlled Trials of Rehabilitation Services in the Post-acute Phase of Moderate and Severe Traumatic Brain Injury – A Systematic Review - Røe, Cecilie; Tverdal, Cathrine; Howe, Emilie Isager; Tenovuo, Olli; Azouvi, Philippe; Andelic, Nada (Frontiers in Neurology, 2019)
Background and aims: There is a gap in knowledge regarding effective rehabilitation service delivery in the post-acute phase after traumatic brain injury (TBI). Recently, Gutenbrunner et al. proposed a classification system for health-related rehabilitation services (International Classification System for Service Organization in Health-related Rehabilitation, ICSO-R) that could be useful for contrasting and comparing rehabilitation services. The ICSO-R describes the dimensions of Provision (i.e., context of delivered services), Funding (i.e., sources of income and refunding) and Delivery (i.e., mode, structure and intensity) at the meso-level of services. We aim to: -Provide an overview of randomized, controlled trials (RCTs) with rehabilitation service relevance provided to patients with moderate and severe TBI in the post-acute phase using the ICSO-R as a framework; and -Evaluate the extent to which the provision, funding and delivery dimensions of rehabilitation services were addressed and differed between the intervention arms in these studies. Materials and methods: A systematic literature search was performed in OVID MEDLINE, EMBASE, CINHAL, PsychINFO, and CENTRAL, including rehabilitation interventions with RCT designs and service relevance targeting moderate and severe TBI in the post-acute phase. Results: 23 studies were included. More than two-thirds of the studies were conducted in a hospital-based rehabilitation setting. The contrast in Context between the intervention arms often co-varied with Resources. The funding of the services was explicitly described in only one study. Aspects of the Delivery dimension were described in all of the studies, and the Mode of Production, Intensity, Aspects of Time and Peer Support were contrasted in the intervention arms in several of the studies.) A wide variety of outcome measures were applied covering several domains of the International Classification of Functioning, Disability and Health (ICF). Conclusion: Aspects of service organization and resources as well as delivery may clearly influence outcome of rehabilitation. Presently, lack of uniformity of data and collection methods, the heterogeneity of structures and processes of rehabilitation services, and a lack of common outcome measurements make comparisons between the studies difficult. Standardized descriptions of services by ICSO-R, offer the possibility to improve comparability in the future and thus enhance the relevance of rehabilitation studies.